2018
DOI: 10.3390/en11092389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Densification Conditions on Specific Energy Requirements and Physical Properties of Compacts Made from Hop Cone

Abstract: Hop cones, due to their essential flavor, are one of the four main ingredients for beer production. The paper reports the results on an investigation of the densification process of hop cones. This experiment investigated (i) the effects of compression pressure in the range of 40 to 80 MPa and pressure application time in the range of 10 to 40 s on the final density and durability of the compacts made from hop cones and ii) the specific compression energy required for the process. The specific compression ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…of CC or CS additives, and at a higher dose of 0.15 g, L s = 67.2 kJ·kg −1 [ 25 ]. Hop cones with 10% moisture content, compacted under the pressure of 40–80 MPa, required lower specific compression energy (14.20–24.48 kJ·kg −1 ) [ 31 ]. For energy-related reasons, it would be beneficial if the L s was less; however, the greater compaction work performed indicates a greater back pressure to be overcome.…”
Section: Resultsmentioning
confidence: 99%
“…of CC or CS additives, and at a higher dose of 0.15 g, L s = 67.2 kJ·kg −1 [ 25 ]. Hop cones with 10% moisture content, compacted under the pressure of 40–80 MPa, required lower specific compression energy (14.20–24.48 kJ·kg −1 ) [ 31 ]. For energy-related reasons, it would be beneficial if the L s was less; however, the greater compaction work performed indicates a greater back pressure to be overcome.…”
Section: Resultsmentioning
confidence: 99%
“…These methodologies for BSG recycling often require a pre-treatment phase, which is typically a drying process. However, the drying phase represents an energy-intensive process [38], which could raise the costs for the breweries [39]. Jackowski et al (2020) [40] have investigated the possibility of using hydrothermal carbonization process (HTC) as a pretreatment of BSG for subsequent use as a biorefinery feedstock.…”
Section: Different Utilization Routes Of Bsg An Alternative To Composting-an Overviewmentioning
confidence: 99%
“…The first part is the optimization of the processing parameters. Based on such research, it has been found that proper ranges of parameters, such as moisture content, particle size, and compression rate, could lead to low energy consumption and high pellet quality (Niccolò et al 2018;Chen et al 2019). However, the optimal ranges vary for different biomass materials (Whittaker and Shield 2017).…”
Section: Introductionmentioning
confidence: 99%